2004
DOI: 10.1007/s10157-004-0278-y
|View full text |Cite
|
Sign up to set email alerts
|

The beneficial effect of effective control of anemia on hyperinsulinemia and hypoxemia in a hemodialysis patient with corrected transposition of the great arteries

Abstract: We report the beneficial effect of control of anemia on hyperinsulinemia and hypoxemia in a hemodialysis patient with corrected transposition of the great arteries. The patient's hemoglobin (Hb) level of 10.3 g/dl on admission represents good control for hemodialysis (HD) patients, but it was too low for this patient with secondary polycythemia because of a right-to-left shunt. Control of anemia for a 10-month period was followed by a marked increase in Hb level (from 10.3 g/dl to 13.9 g/dl) and in aerobic wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Serum ferritin concentration is marker of iron stores in the body 13 as well as systemic inflammation 6 and is associated with the amount of heme-iron intake: hemeiron intake 14 and anemia [14][15][16] also have been reported to be independently associated with insulin resistance or metabolic disease. Furthermore, central adiposity, an important risk factor of insulin resistance, is also associated with ferritin level.…”
Section: Introductionmentioning
confidence: 99%
“…Serum ferritin concentration is marker of iron stores in the body 13 as well as systemic inflammation 6 and is associated with the amount of heme-iron intake: hemeiron intake 14 and anemia [14][15][16] also have been reported to be independently associated with insulin resistance or metabolic disease. Furthermore, central adiposity, an important risk factor of insulin resistance, is also associated with ferritin level.…”
Section: Introductionmentioning
confidence: 99%
“…Among patients with chronic renal failure treated with hemodialysis, moderate to severe anemia was also a risk factor for insulin resistance ( 10 , 11 , 12 , 27 ). Partial correction of anemia with erythropoietin was shown to reduce insulin resistance as well as reduce insulin secretion ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of chronic renal failure patients treated with multiple episodes of hemodialysis reported that low hematocrit (Hct) may induce tissue hypoxia and cause insulin resistance. Erythropoietin treatment improves the anemic state and reduces insulin resistance in these patients ( 10 , 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…1 According to above explanation, almost 90 percent of patients with a glomerular filtration rate (GFR) short of what 25 to 30 mL / min have anemia, numerous with Hemoglobin levels below 10 g/dL. 2 Without treatment, the anemia of chronic kidney disease (CKD) cause number of physiologic abnormalities and pathological problems including decreased tissue oxygen delivery and utilization, 3 , cardiac enlargement,increased cardiac output ,angina, ventricular hypertrophy, congestive heart failure, 4,5 decreased cognition and mental acuity, menstrual issues, decreased nocturnal penile tumescene, and impaired immune achievements. 6 Normocytic normochromic anemia is most overwhelming s finding of Chronic Renal Disease patients, in additions, anemia may result in growth retardation and decreased intellectual efficiency in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%